STUDI APLIKASI KINERJA TURBIN ULIR ( SCREW TURBINE ) PADA SISTEM SIRKULASI ALIRAN AIR DENGAN MENGGUNAKAN PENGUJIAN MEKANIS - , YOPI MIHEL SESA, Ir . Samsul Kamal, M.Sc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The utilization of water energy resources as a renewable energy source generally requires a high investment. But in a small scale, it can be done using renewable technologies to make it implemented. A form of the utilization is to use a Micro Hydro Power Plant (MHP). The main components of MHP is a turbine, which used in this study is screw turbine. The use of screw turbine began in Europe in late 2007, but in Indonesia, it started in 2009 in West Java. Screw turbine has high efficiency and can operate at a low head, which appropriate with water potential energy with has head low in Indonesia. As a new turbine technology, it is still very little theory or references that are available related to the design of turbine screw. Lots of design performance parameters are not well understood, one of which is screw turbine performance by utilizing the flow of water circulation. This study conducted experiments that tried to determine the relationship of water flow towards the turbine rotation, torque, power and efficiency at all three variations of valve openings for the flow of water are 0.0491 mm2, 0.0245 mm2 and 0.0123 mm2, respectively. Based on the results of extensive testing of turbine threaded openings valve are 0.0491 mm2 better than 0.0245 mm2 and 0.0123 mm2.